Antibakteri Ekstrak Etanol Serbuk Kering Sargassum cristaefolium Terhadap Bakteri Escherischia coli dan Salmonella thyposa - Kartikaningsih, Hartati (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2020)
Sargassum cristaefolium dried powder can be used as food and fed additives as well as Â a beverage powder, contained some minerals and terpenoid active ingredients. This study aimed to determine the anti-bacterial activity of Sargassum cristaefolium dried powder on the inhibition of Escherischia coli and Salmonella thyposa bacteria in vitro. The research showed that the dried powder of Sargassum cristaefolium had better inhibition on Salmonella thyposa (2.3 mm) compared to Escherischia coli (1.2 mm) although it was classified as weak bactericidal. Sargassum cristaefolium dried powder showed positive testing for alkaloids, flavonoids, terpenoids and tannins and does not contain saponins, had low toxicity (LC50 322 ppm). The LCMS test showed a peak at 2.16 retention time with a molecular weight of 339.39 m/z. The structure of the Sargassum cristaefolium antibacterial active ingredient should be clarified using C-NMR and H-NMR.